2016
DOI: 10.1055/s-0042-104061
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods for the Estimation of Body Composition in Highly Trained Wheelchair Games Players

Abstract: The purpose of this study was to assess the agreement in body composition measurements of wheelchair athletes using skinfolds, bio-impedance analysis (BIA) and air displacement plethysmography (ADP) relative to dual-energy X-ray absorptiometry (DXA). A secondary objective was to develop new skinfold prediction equations to estimate %fat for this sample. 30 wheelchair games players were recruited and the body composition outcomes of BIA, ADP, and skinfolds were compared to the DXA outcomes by a paired-samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 30 publications
3
32
0
4
Order By: Relevance
“…The BMI (20.8-22.5 kg/m 2 ), WC (67.8-75.4 cm) and waist/hip ratio (0.87-0.95) in wheelchair athletes with SCI [15] were much lower than in our group. Goosey-Tolfrey et al [16] measured the percentage fat mass by, among others, skinfolds (19.1% fat mass) and BIA (18.4% fat mass) in 30 wheelchair games players and found 6-10% lower values. These results indicated that the body composition of the participants of the HandbikeBattle is mostly comparable to the body composition of general wheelchair users with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…The BMI (20.8-22.5 kg/m 2 ), WC (67.8-75.4 cm) and waist/hip ratio (0.87-0.95) in wheelchair athletes with SCI [15] were much lower than in our group. Goosey-Tolfrey et al [16] measured the percentage fat mass by, among others, skinfolds (19.1% fat mass) and BIA (18.4% fat mass) in 30 wheelchair games players and found 6-10% lower values. These results indicated that the body composition of the participants of the HandbikeBattle is mostly comparable to the body composition of general wheelchair users with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…17 Percentage body fat was not calculated as no validated four-site skinfold predication equations currently exists in the literature for disabled population groups with substantial body asymmetry as a result of amputation or lower body muscular atrophy due to spinal cord injury. 15…”
Section: Anthropometrymentioning
confidence: 99%
“…International, West Sussex, UK) were taken for all participants (n = 17) in a seated position from the biceps, triceps, subscapular and suprailliac to calculate the sum of skinfolds (mm). However, to get a true reflection of body composition for individuals with an SCI, according to recent studies, [12] a DXA scan was performed for seven of SCI using a Lunar Prodigy Advance DXA scanner (GE Lunar, Madison, WI, USA) following procedures procedures previously described [18]. The compartments measured were total body fat and lean tissue mass.…”
Section: Body Composition Skinfold Measurements (Harpenden Skinfold mentioning
confidence: 99%